Hadith HR. Bukhari No. 5559 about Saying Good or Keeping Silent in Responding to Verbal Bullying Cases at School - Rizky Hanifah; Nur Kholis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article aims to examine HR. Bukhari No. 5559 regarding saying good or being silent when looking at the phenomenon of verbal bullying at school. This research is qualitative research using library research methods. The conclusion of this article is that verbal bullying is an act that is prohibited in Islam. In the school environment, verbal bullying can have a negative impact on students, whether they are perpetrators or victims. This hadith provides direction to teachers, students and all elements in the school environment to build quality interactions to support the learning process. The word khair in the hadith of Bukhari's History No. 5559 contains good meanings that are in accordance with religious teachings and in line with societal norms. So the words delivered by teachers and students must be in line with the meaning of khair. If the words you say are not useful, silence will be the best solution to protect yourself from danger.